Experimental investigations on diesel engine fuelled with methyl esters of cotton seed oil. (1st January 2013) - Saravanan, M.; Anbarasu, A.; Loganathan, M.
In this investigation, cotton seed methyl ester (CSME) was prepared by transesterification using potassium hydroxide (KOH) as catalyst. The engine performance was analysed with different blends of biodiesel and was compared with neat diesel. It was concluded that the lower blends of biodiesel are closer to diesel as far as thermal efficiency is concerned. In the lower blends, the brakes specific fuel consumption is also comparatively reduced. The smoke density also increases for the blends of methyl ester of cotton seed oil diesel compared to neat diesel operation. The oxides of nitrogen (NOx) emission level are decreased with the blends of methyl ester of cotton seed oil compared to neat diesel. The results proved that the use of biodiesel (produced from cotton seed oil) in compression ignition engine is a viable alternative to diesel.